2016
DOI: 10.1093/pcp/pcw165
|View full text |Cite
|
Sign up to set email alerts
|

Oil Biosynthesis in Underground Oil-Rich Storage Vegetative Tissue: Comparison ofCyperus esculentusTuber with Oil Seeds and Fruits

Abstract: Cyperus esculentus is unique in that it can accumulate rich oil in its tubers. However, the underlying mechanism of tuber oil biosynthesis is still unclear. Our transcriptional analyses of the pathways from pyruvate production up to triacylglycerol (TAG) accumulation in tubers revealed many distinct species-specific lipid expression patterns from oil seeds and fruits, indicating that in C. esculentus tuber: (i) carbon flux from sucrose toward plastid pyruvate could be produced mostly through the cytosolic glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 98 publications
6
37
0
Order By: Relevance
“…In this study, we indeed observed the high Suc-to-hexose ratios over the tuber development of C. esculentus (Fig. 1 ), where oil accumulation began at around 50 DAS [ 40 ].…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…In this study, we indeed observed the high Suc-to-hexose ratios over the tuber development of C. esculentus (Fig. 1 ), where oil accumulation began at around 50 DAS [ 40 ].…”
Section: Resultsmentioning
confidence: 69%
“…Our previous transcriptome analyses of C. esculentus tubers from three representative samples at 50, 85 and 120 DAS of developmental stages (i.e. the early stage of 40–50 DAS, the middle stage of 50–85 DAS and the late stage of 85–120 DAS, corresponding to the stage of low oil level and oil accumulation rate, medium oil level but high oil accumulation rate, and high oil level with low oil accumulation rate, respectively) have indicated that 41.05% of total 99,558 transcripts were successfully annotated [ 40 ]. Among them, 488 annotated transcripts were involved in carbohydrate metabolism, of which 355 unigenes were found to be expressed in the developing C. esculentus tubers (Additional file 1 : Table S1d).…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis of connectivity in the none-preserved module at the PR phase reveals another gene, LACS7, a part of peroxisome proliferator-activated receptors (PPAR) and Adipocytokine signaling pathways [55], as another important gene. Newly synthesized free fatty acids (FAs) need to activate to acyl-CoA form by LACS to involves in the glycerolipid metabolic pathways, indicating the critical roles of LACS in FA metabolism [56]. In Arabidopsis, a family of nine genes encoding LACS protein has been identified to play their roles in various aspects of lipid metabolism at different subcellular localizations.…”
Section: Kegg Pathway P-value Genesmentioning
confidence: 99%
“…Some studies have used comparative proteomics approaches on lipid regulation between different types of oilseeds [14,47]. In a recent study, Yang et al [48] conducted a comprehensive and systematic transcriptome analysis of Cyperus esculentus, along with a comparative analysis of other oil-rich tissues of seeds and mesocarp to understand oil biosynthesis in vegetative tissues of diverse species. Cyperus esculentus is unique in that it can accumulate oil in its tubers.…”
Section: Investigation Of Oil Yield Using Omicsmentioning
confidence: 99%
“…However, upon maturation, chlorophyll content continued to increase, but leaf nitrogen decreased dramatically until leaf 32. No significant changes in either chlorophyll and nitrogen content were observed in leaves [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. Following this study, the distribution of natural 13 C in oil palm leaves was investigated.…”
Section: Leaf Metabolomics Studiesmentioning
confidence: 99%